Obtenção de acetato de celulose a partir de bagaço de cana-de-açúcar e análise de degradação in vitro - Silva, Joelen Osmari da (2019)
The Sugarcane (Saccharum officinarum L.) is currently one of the main agricultural products. Considering the high production of sugarcane bagasse in Brazil and in the world, the objective was to obtain pre-treated sugarcane bagasse cellulose acetate (CA) membranes in different granulometrie. For this, was used the pulping processes acetosolve, bleaching with sodium chlorite and heterogeneous reaction of acetylation. Also, was verified the in vitro degradation of the membranes in PBS solution under body conditions for four months. And, finally, the possibility of application as biomaterial by cytotoxicity analysis in culture of human fibroblastic cells. The sugarcane bagasse was chemically characterized. The samples obtained at each stage of the processing were characterized by SEM and FTIR and the degree of membrane transparency was evaluated through UV-VIS. The membranes obtained from the fibers retained in the 20 mesh sieve presented greater transparency and mechanical resistance. In this way, they were chosen for the analysis of in vitro degradation in PBS solution and evaluation of cytotoxicity. The bleached pulp and the CA had the degree of polymerization determined by viscosimetry. The degree of bleaching of the bleached pulp was determined by whiteness. The degree of substitution (DS) of the CAs obtained was determined by retro-labeling. The membranes subjected to degradation were analyzed by pH variation, mass loss, DMTA and UV-VIS from PBS solutions. Cytotoxicity was assessed by MTT analysis and confocal microscopy. It was possible to observe that the processes were more efficient with the fibers of larger granulometry and that these are possible biomaterials, because there was cell proliferation during the analysis of cytotoxicity. However, it was not possible to guarantee that during the analysis period there was no degradation of the membranes. Further analyzes are necessary to conclude these results.